The Role of Blockchain in IT Project Management: Literature Review - Sultan S. Alharbi; Mehmet Sabih Aksoy (Genius Journals, 2023)
Many projects fail due to sustainability issues. Lack of transparency, inadequate information communication management and other factors resulting in poor Project Management (PM) are among the explanations that cause projects to fail in developing countries. In many areas, including project management, blockchain offers a fresh approach to altering traditional paradigms through innovative means. Literature offers support for the values and challenges posed by PM and blockchain, and then it interrelates with them. Therefore, this research was geared towards investigating the role of blockchain in improving PM. According to this review, blockchain technology offers a diverse array of functionalities and capabilities that aid in project management. The guideline for emerging blockchain research in project management is also outlined in this review. When PM is integrated with blockchain, it can enhance cost control, process automation, transparency, and stakeholder communication. This results in a successful project.
Keywords: Blockchain; Project Management; Smart contract